La ética de la autoconservación y la teoría de los deberes políticos en el Leviatán de Hobbes* - Cortéz Rodas, Francisco (2002)
“The Ethics of Self-Preservation and the Theory of Political Duties in Hobbes’ Leviathan”. In order to present the political argument in Thomas Hobbes’ Leviathan, the author proposes an interpretation of his doctrine developed by Alfred Taylor, Howard Warrender and Michael Oakeshott. According to this interpretation, Hobbesian ethics, as developed in his theory of the laws of nature, once distinguished from his selfish psychology, shows itself as a strict deontological ethics, very close to Kant’s. The second part of the paper attempts to show the problems with this interpretation of Leviathan.